2000
DOI: 10.1002/(sici)1521-3765(20000515)6:10<1773::aid-chem1773>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Supported Carbene Complexes of Palladium: Well-Defined, Air-Stable, Recyclable Catalysts for the Heck Reaction

Abstract: N-Heterocyclic dicarbene chelate complexes of formula [cis-CH2N(H)C=C(H)N(R)C2PdX2] (X = Br, I; R = (CH2)nOH; n = 2, 3) have been prepared and structurally characterized (for X= I, n = 2). The complexes were immobilized on a functionalized polystyrene support (Wang resin) through one of the oxygen centres. The complexes efficiently catalyze the Heck reaction of activated and non-activated arylbromides, are recyclable under aerobic conditions and exhibit hardly any leaching, which is in line with our theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(81 citation statements)
references
References 14 publications
3
75
0
3
Order By: Relevance
“…For example, NHC complexes of Pd have been investigated for their utility in the Heck coupling reaction in organic synthesis [3]. The Heck coupling reaction utilizes NHC complexes as catalysts (scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…For example, NHC complexes of Pd have been investigated for their utility in the Heck coupling reaction in organic synthesis [3]. The Heck coupling reaction utilizes NHC complexes as catalysts (scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical bonding between NHCs and group 11 metals have been investigated theoretically (Nemcsok et al 2004;Hu et al 2004). Moreover, theoretical studies of the electronic structure of transition metal complexes with NHCs ligand have been recently carried out by other group (Schwarz et al 2000;Weskamp et al 1999;Lee et al 2004). The fact was that, the type of NHC ligands that have been developed by Arduengo et al [1991] have found recent use in the synthesis of molecular gold(I) fluoride and chloride complexes.…”
mentioning
confidence: 99%
“…To improve recyclability of such NHC complexes, great efforts have been devoted to develop heterogeneous NHC organometallic catalytic systems34567. Imidazolium-based ionic salts are well known to be excellent precursors of metal NHCs, and various solid supports containing imidazolium groups have been used as precursors of heterogeneous palladium NHCs3456.…”
mentioning
confidence: 99%
“…To improve recyclability of such NHC complexes, great efforts have been devoted to develop heterogeneous NHC organometallic catalytic systems34567. Imidazolium-based ionic salts are well known to be excellent precursors of metal NHCs, and various solid supports containing imidazolium groups have been used as precursors of heterogeneous palladium NHCs3456. In the context, di- or poly-cationic imidazolium salts were well known to possess superior performances over monocationic analogues, but heterogeneous catalytic systems consisting of stable chelating palladium NHC units were seldom explored34, despite the discrete chelating palladium NHC complexes were frequently investigated in catalysis2.…”
mentioning
confidence: 99%
See 1 more Smart Citation